(untitled) (Journal on studies and research of academic knowledge, 2009)
The present work has a fundamental aim to compare the effects of the hydric erosion of the soils cultivated in two systems of plowing: the convencional plowing or Conventional system (CS) and the Direct Plowing (DP). The convencional plowing consists in the preparation or remotion of the soil before the plow with implements of making the soil ready to be planted; but the Direct Plowing is the practice of Crop of plants without physical preparation of the soil, maintaining the plant or stubble of the previous crop in the surface, it involves no remotion of the soil, it is only making a roturation in the field as a place to through the seed. The demostratives fields are situated in a region with a soil of basáltic origin corresponding to the classification of Rhodic paleudults very fine clayey.The type of study was quantitative – comparative using the methods of Correlation and index of Potential of Degradation of Soil (IPD). The plots analysed were of the following dimensions: 40 m of width by 100 m of long each one (4.000 m²), the average of earring of the plots is of 8 %.The agricultural crops plowed were wheat and soya; all the plots had been plowed the same day and received the same chemical fertilization. The results of the IPD for both systems were: CS: 0,688 falls inside the HIGH rank index of potentiality of degradation of the soil, what indicates that in the conventional system observed, launched a result that conform to the method of analysis means an attention to the crop system in similar conditions of topographyweather, type of soil, etc., so much that in DP the level of potentiality is absolutely minor (0,015). This fact refers equally in the comparative of the quantity erosioned in the period of study in both systems, having around 98 % of the losses gave in the conventional system of crop having in account the total IPD. This same fact is refered in the values that gave the porcentual of soil erosioned thus the 93, 34 % corresponds to this system of labourThe porcentual for both systems launched the following values: 1, 66 % of soil eroded there was in the DP and 93, 34 % of soil erosioned in the CS.